Biological, clinical features and modelling of heterozygous variants of glycoprotein Ib platelet subunit alpha (GP1BA) and glycoprotein Ib platelet subunit beta (GP1BB) genes responsible for constitutional thrombocytopenia. (29th September 2022) - Dib, Fatema; Quéméner, Agnès; Bayart, Sophie; Boisseau, Pierre; Babuty, Antoine; Trossaërt, Marc; Sigaud, Marianne; Ternisien, Catherine; Drillaud, Nicolas; Eveillard, Marion; Guillet, Benoit; Béné, Marie C.; et al.
Summary: Constitutional thrombocytopenias are rare disorders, often difficult to discriminate from acquired thrombocytopenias. More than 80 genes have been described as being at the origin of these diseases. Among them, several variants of the glycoprotein Ib platelet subunit alpha ( GP1BA ) and glycoprotein Ib platelet subunit beta ( GP1BB ) genes, coding for the GpIb‐IX‐V glycoprotein complex, have been reported in the literature. The study reported here aimed at describing newly identified monoallelic anomalies affecting the GP1BA and GP1BB genes on a clinical, biological and molecular level. In a cohort of nine patients with macrothrombocytopenia, eight heterozygous variants of the GP1BA or GP1BB genes were identified. Five of them had never been described in the heterozygous state. Computer modelling disclosed structure/function relationships of these five variants.